The underground economy : a selective history, theory and practical guide to localised underground deviance in New Zealand - Monckton, Ben (Massey University, 2001)
In order to assist the reader in conceptualising the notions I wish to describe in this thesis, it may be useful to portray my ideas by way of this preface. This will take the form of the perspective, initial focus and development of my research. After completing my degree I initially lived with, and was consequently interested in looking at people and groups that did not want to interact within the mainstream New Zealand capitalistic infrastructure. These people (myself included) were largely made up of those who felt (idealistically?) that through focusing on money and material gain capitalism had lost most of its appeal as a way of life. Consequently these "hippies" and members of alternative communities choose to live in various differing fashions. I then came to realise that although many of these people felt they were no longer part of society, or more particularly capitalism (this appeared as a reoccurring theme among the people I spoke with), that was their one constraint. They had to have money in order to operate in relative autonomy from the rest of society. In order to get away from the "rat race" one had to purchase some land, which in turn needed developing. In order to gain money one usually had to participate in the "rat race". This led me to a change in philosophical tack; I began to see a difference in those that I (possibly unfairly) saw as running away from capitalism and those who cunningly hid from it. [From Preface]
Keywords: New Zealand Economic aspects; Informal sector (Economics); Deviant behavior; Criminal behavior; Social conditions; Economic conditions